The US Presidential Election Process - Khwanmuang, Komet (Journal of MCU Social Science Review, 2016)
The United States of America Constitution 1787 changed the form of statefrom the old constitution named as Confederation to the form of Federation as composited states called the name of the country as the United States of Americathat in the year of 1787 had only 13 states. At present, the United States of America has 50 states. Moreover, the constitution of the United States of America1787 enacts that the United states of America have the form ofgovernmentaccording to Presidential system that it has the President as the Head of State andalso Head of Government. The presidential Institution is the Supreme ExecutiveBranch of the country that it is mentioned since the Constitutional Convention atPhiladelphia in Pennsylvania State in 1787 and has thePresidential Election up to election since the stage of getting the Presidential Nominee on behalf of politicalparties and stage of Presidential election by the Popular Vote of the people whohave the right to vote and the stage of Presidential election by Electoral Collegenames as Electoral Vote. now. The objective of This article is to study the stage or process of Presidential